Sperm evaluation in strains of Nile tilapia, Oreochromis niloticus (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The reproductive characteristics of tilapia species used for large-scale production is critically important for breeding management. Although Nile tilapia (Oreochromis niloticus) is one of the most cultivated species globally, little is known about its sperm characteristics. Therefore, the objective of this study was to evaluate and compare the reproductive parameters of three tilapia strains before and after cryopreservation. Nile tilapia specimens from three strains, Supreme (SUP), Premium Aquabel (PA), and Chitralada (CHI) (90 specimens in total, 30 from each strain), were examined. All morphometric measurements were highest in PA. CHI had the highest sperm motility and speed, although less than half the sperm concentration of SUP. PA had a similar sperm speed and concentration to CHI, although its sperm motility was similar to that of SUP. SUP had a relatively high sperm viability and higher percentages of sperm without dislocation than PA and CHI. However, all strains showed similar rectilinear dislocation. Except for PA DNA integrity, SUP showed the best results before cryopreservation. From the results it was not possible to identify an ideal marker for semen quality, due to the differences observed between specimens from the same fish. However, the results regarding efficient sperm cryopreservation in the present study are important for the genetic screening and development of these strains in aquaculture.